2016
DOI: 10.3389/fmicb.2016.00792
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Genomics and Proteomics in the New Isolated Bacillus thuringiensis X022 Revealed the Metabolic Regulation Mechanism of Carbon Flux Following Cu2+ Treatment

Abstract: Bacillus thuringiensis (Bt) X022 is a novel strain isolated from soil in China, and showed strong insecticidal activity against several Lepidopteran pests. In this work, we performed whole genome sequencing of this Bt strain using the next-generation sequencing technology, and further conducted a comparative analysis with the proteomics data of the specific spore-release period based on LC-MS/MS approach. The Bt X022 genome consisted of one circular chromosomal DNA and seven plasmids, which were further functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(48 reference statements)
2
4
0
Order By: Relevance
“…Cu 2+ can increase the expression level of insecticidal proteins of BtX023, and the enhanced toxicity to pests is similar to previous reports [16,20]. Previous reports indicated that Cu 2+ ions considerably affect the synthesis of PHB but does not significantly improve it.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cu 2+ can increase the expression level of insecticidal proteins of BtX023, and the enhanced toxicity to pests is similar to previous reports [16,20]. Previous reports indicated that Cu 2+ ions considerably affect the synthesis of PHB but does not significantly improve it.…”
Section: Discussionsupporting
confidence: 89%
“…Subsequently, the urea concentration in the sample was diluted to 1 M and subjected to enzymatic hydrolysis. These enzymatic fragments were separated and desalted by 2D-HPLC equipped with a strong cation-exchange column (BioBasic SCX; 0.32 mm × 100 mm, 5 μm) and a reversedphase column (BioBasic-C18; 0.1 mm × 150 mm, 5 μm) and then analyzed by LC-MS/MS using the Thermo Q-Exactive Plus (ThermoFisher, San Jose, CA, USA) equipped with an ultra-high performance liquid chromatography unit (Thermo Scientific Dionex Ultimate 3000) and a Nanospray Flex Ion-Source (Thermo Scientific) [16,20,[28][29][30]. After the original mass spectrometry data were converted into the mgf format file by the corresponding tools, the Maxquant software (according to the Bt protein library) was used to search for the identification and quantitative information extraction of the corresponding database.…”
Section: Lfq-ms Analyzingmentioning
confidence: 99%
“…The quantity of the proteins expressed at the three different growth phases for the Bt isolates E-SE10.2 and O-V84.2 were 10.2–3.5% and 10.4–8.2%, 8.3–2.8%, respectively, of their genome encoded sequences. This low percentage of expressed proteins detected indicates that, in our experimental conditions, we only detect a small part of the predicted proteins by the genome data prediction, a phenomenon that has also been found in other studies [ 21 , 22 ]. The low percentage of detected expressed proteins should not be interpreted as that the rest of the proteins cannot be expressed, since they could do it under different growth conditions.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, the development of the mass spectrometry (MS)-based proteomics has enabled the detection of proteins from complex mixtures from different stages of a microorganism [ 18 ]. The combination of the genomic and proteomic approaches is a very successful approach for validation and correction of predicted genomic coding information in a wide variety of organisms [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, both genomic and proteomic techniques are utilized in Bt studies, although the number of comparative proteomics papers [ 10 , 11 ] is considerably smaller than that of works on comparative genomics [ 12 , 13 , 14 , 15 ]. Ideally, the genomic and proteomic approaches should be used in parallel in order to detect virulence factors that are either missing in the proteome screening [ 16 ] or misannotated in the genomic data [ 17 ]. This combined approach is especially relevant when concerning the identification of Cry toxins, which tend to fall out of the scope in both proteomic [ 11 , 16 ] and genomic [ 18 ] studies.…”
Section: Introductionmentioning
confidence: 99%